Klasyfikacja gospodarstw rolniczych na podstawie danych w postaci szeregów czasowych - Kisielińska, Joanna (Classification of Farms Based on Time Series Data, 2008)
In the paper the construction of classification models for farms based on time series data is proposed. In the suggested approach data concerning farms were aggregated using the weighted moving average method. The proposed method was tested on a sample of 704 farm households for various smoothing constants and various combinations of weights. Two types of models were built in the form of linear discriminant functions and obtained by neural networks which enabled a comparison of linear and nonlinear approach to the classification problem. It turned out that all function and network models built based on data representing several preceding periods were better than models built based on data representing one year. Besides all network models were better than their function counterparts but the differences were slight.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 519-526